2008
DOI: 10.1017/s175173110800253x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of liquid feeding at different water-to-feed ratios on the growth performance of growing-finishing pigs

Abstract: The study examined the growth performance of pigs offered liquid feed or dry feed on either a restricted or an ad libitum basis, and whether their growth performance was further influenced by the water-to-feed ratio. The study was split into two parts to enable unrestricted (trial 1; n 5 64) and restricted (trial 2; n 5 48) feeding to be compared. Male pigs were randomly allocated to six dietary treatment groups. A standard dry pellets diet (D) was offered either as: (i) unrestricted ration (UR); (ii) restrict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 24 publications
2
22
0
3
Order By: Relevance
“…Liquid feeding may also improve the intestinal health of pigs (Deprez et al, 1987) and performance of pigs fed diets in a liquid form is often improved compared with pigs fed dry diets (Hurst et al, 2008). An improvement in nutrient digestibility has also been demonstrated in diets based on barley and wheat (Pedersen and Lindberg, 2003;Lyberg et al, 2006), and performance and apparent total tract digestibility (ATTD) of P in a maize-soybean meal diet was improved if feed was soaked prior to feeding (Liu et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Liquid feeding may also improve the intestinal health of pigs (Deprez et al, 1987) and performance of pigs fed diets in a liquid form is often improved compared with pigs fed dry diets (Hurst et al, 2008). An improvement in nutrient digestibility has also been demonstrated in diets based on barley and wheat (Pedersen and Lindberg, 2003;Lyberg et al, 2006), and performance and apparent total tract digestibility (ATTD) of P in a maize-soybean meal diet was improved if feed was soaked prior to feeding (Liu et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In another experiment using large pigs held without feed for 6 h, Gonyou and Lou (2000) found that pigs consumed 500 g of feed nearly 3 times faster when it was premixed with an equal amount of water. Hsia and Lu (1985) and Hurst et al (2008) also have reported a considerably faster eating rate for wet-fed compared with dry-fed pigs. In the current experiment, providing access to water with feed likely increased eating speed for pigs using the wet-dry feeder.…”
Section: Discussionmentioning
confidence: 94%
“…Water to feed ratio, or dry matter content in liquid diet, may affect pig growth performance [2224] and nutrient digestibility [25, 26]. For example, Hurst et al [24] found that feed efficiency of growing-finishing pigs was improved by 3.6% and feed intake was reduced by about 3% as the ratio of water to feed was increased from 1.5:1 to 3:1 when pigs were fed at the level of 90 to 95% of ad libitum feed intake. In the present study, dry matter content in feed was kept similar, with an attempt to remove the potential confounding effect of dry matter content.…”
Section: Discussionmentioning
confidence: 99%